2013
DOI: 10.5194/isprsarchives-xl-1-w1-105-2013
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Glacier Surface Area Using Spaceborne Sar Imagery

Abstract: ABSTRACT:Glaciers are very important climate indicators. Although visible remote sensing techniques can be used to extract glacier variations effectively and accurately, the necessary data are depending on good weather conditions. In this paper, a method for determination of glacier surface area using multi-temporal and multi-angle high resolution TerraSAR-X data sets is presented. We reduce the "data holes" in the SAR scenes affected by radar shadowing and specular backscattering of smooth ice surfaces by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In the case studies performed in cryospheric regions, we can conclude that HR RS data is the best fit for the information extraction. CSIR [45] [58] [71]- [81], ensemble classifiers [38], RF [68] and spectral-shape approach based on OOC methods [60] are the best suited methods as compared to traditional classification approaches. The accuracy shown by these classifiers ranges between 85% and 97% (approximately).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…In the case studies performed in cryospheric regions, we can conclude that HR RS data is the best fit for the information extraction. CSIR [45] [58] [71]- [81], ensemble classifiers [38], RF [68] and spectral-shape approach based on OOC methods [60] are the best suited methods as compared to traditional classification approaches. The accuracy shown by these classifiers ranges between 85% and 97% (approximately).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Taking into account the small spatial scale of the image range, the decision tree classification algorithm was used for the fast and robust classification calculation. The classification results obtained from the RF decision tree algorithm (Fang et al 2013) are shown in Fig. 4a, and the area of glacier is about 943.4 km 2 .…”
Section: Insar Processingmentioning
confidence: 99%
“…Unlike the passive visual spectrum sensors onboard the Landsat missions, synthetic aperture radar (SAR) actively detects microwave reflection signals that pierce through cloud cover and darkness [17][18][19], making it a useful tool in alpine and polar glacier velocity determination. Spaceborne SAR sensors onboard the European Space Agency's (ESA) ERS-1/2 missions launched in the 1990s created a tandem constellation of satellites that achieved sub-30 m spatial resolution with individual 35 day repeat cycles [20].…”
Section: Introductionmentioning
confidence: 99%
“…Both temporal and spatial resolution improved in the 2000s with the deployment of TerraSAR-X, granting a sub-16 m pixel SAR scanning mode and an 11-day repeat cycle [19]. In 2014 and 2015, the ESA launched the Sentinel-1a and Sentinel-1b (S1a/S1b) satellites, respectively, providing 10 m resolution coverage on a tandem repeat cycle of 6 days, further improving accuracy and precision [18]. Individual researchers can obtain SAR-based velocity fields using the ESA's SeNtinel Analysis Platform (SNAP).…”
Section: Introductionmentioning
confidence: 99%